Is patient-centredness in European hospitals related to existing quality improvement strategies? Analysis of a cross-sectional survey (MARQuIS study). (2nd February 2009) - Groene, O; Lombarts, M J M H; Klazinga, N; Alonso, J; Thompson, A; Suñol, R
Abstract : Background: There is growing recognition of patients' contributions to setting objectives for their own care, improving health outcomes and evaluating care. Objective: To quantify the extent to which European hospitals have implemented strategies to promote a patient-centred approach, and to assess whether these strategies are associated with hospital characteristics and the development of the hospital's quality improvement system. Design: Cross-sectional survey of 351 European hospital managers and professionals. Main outcome measures: Patients' rights, patient information and empowerment, patient involvement in quality management, learning from patients, and patient hotel services at the hospital and ward level were assessed. The hypothesis that the implementation of strategies to improve patient-centredness is associated with hospital characteristics, including maturity of the hospital's quality management system, was tested using binary logistic regression. Results: In general, hospitals reported high implementation of policies for patients' rights (85.5%) and informed consent (93%), whereas strategies to involve patients (71%) and learn from their experience (66%) were less frequently implemented. For 13 out of 18 hospital strategies, institutions with a more developed quality improvement system consistently reported better results (percentage differences within maturity classification ranged from 12.4% to 46.6%). The strength of association between implementation of patient-centredness strategies and the quality improvement system, however, seemed lower at the ward than at the hospital level. Some associations (OR 2.1 to 5.1) disappeared or were weaker after adjustment for potential confounding variables (OR 2.2 to 3.7). Conclusions: Although quality improvement systems seem to be effective with regard to the implementation of selected patient-centredness strategies, they seem to be insufficient to ensure widespread implementation of patient-centredness throughout the organisation.